Description of Pratylenchoides ojcowensis sp. nov. (Nematoda: Merlinidae) from Polish Jurassic Highland - Winiszewska, Grażyna; Dobosz, Renata; Malewski, Tadeusz; Skwiercz, Andrzej (Zootaxa, 2020)
A new species of the genus Pratylenchoides has been described. It was found in Polish Jurassic Highland, in Ojców National Park. Pratylenchoides ojcowensis sp. nov. was isolated from the soil located around tangled roots of Elymus sp. and Trifolium sp. This species is marked by a conical head in both females and males which is not separated from the body contour and has with 4–5 annuli; a relatively short stylet (20.3–21.3 µm females, 17.7–20.9 µm males) with oval knobs directed posteriorly; the dorsal pharyngeal nucleus located anterior to the cardia (the subventral pharyngeal nuclei located posterior; a pharyngeal lobe of length about two body widths (1.8–2.6); a lateral field with 6 lines in the middle part of body and sometimes with partially areolated outer bands; intestinal fasciculi present; round sperm in the spermatheca in females; a female tail with a maximum of 29 annuli, and an annulated tail terminus. The status of the new species has been verifiied by DNA sequencing and phylogenetic analysis of the 28S rDNA region. The results obtained in the study indicated that P. ojcowensis sp. nov. is most related to P. alkani, P. ritteri and P. nevadensis from which is distinguished by the shape of the female head (conoid vs rounded), shorter stylet in females (20.3–21.3 µm vs 22.0–25.0 µm, 21.0–25.0 µm, 22.0–26.0 µm) and differences in 28S rDNA sequences. In addition (as per the original descriptions Yüksel 1977, Sher 1970, Talavera & Tobar 1996) it is distinguished from P. alkani by smaller number of male’s head annuli (4–5 vs 7–9), from P. ritteri it is distinguished by posteriorly directed stylet knobs (vs directed laterally), from P. nevadensis it is distinguished by oval and posteriorly directed stylet knobs (vs rounded and directed laterally).